Promotion of university students' collaborative skills in open innovation environment - Karine Oganisjana (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
It is argued that the participation in open innovation processes requires a specific set of thinking, skills and behaviours founded on the willingness and readiness to exchange, accept, encourage, cooperate and co-create based on trust and collaboration. The paper presents the results of a study conducted in Riga Technical University with 85 bachelor students within the study course "Economics of entrepreneurship" in the autumn semester of 2014. The course was organised in an open environment, in which students worked in teams for solving real life problems in order to create new products and services. They had the opportunity to act not only within the University framework realising intra-team and inter-team collaboration facilitated by teachers and invited entrepreneurs, but they were also encouraged to collaborate with specialists they needed from outside the University for the realization of their projects. The qualitative content analysis of the texts of the students' reflection revealed how highly students evaluated the potential intergenerational collaboration outside the formal University frames. However their judgements on the advantages of such openness remained mainly at the level of theoretical judgements but were not followed by corresponding behaviour.
Keywords: 650; Open innovation; Openness to experience; University education; Learning for entrepreneurship; Open innovation environment; Students' collaborative skills; Intergenerational collaboration